Pengaruh Teknologi Informasi dan Sistem Informasi Akuntansi terhadap Kinerja UMKM di Kecamatan Medan Johor - Risfadillah Risfadillah; Indah Cahya Sagala; Shabrina Tri Asti Nasution (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study was to determine the effect of information technology and accounting information systems on the performance of MSMEs in Medan Johor District. The sample in this study was 73 respondents of MSME actors in Medan Johor District, using saturated samples. The type of data in this study is quantitative data. The data collection method used was a questionnaire. The data analysis technique used in this study used the Validity Test and Reliability Test. The data was processed using the program (SPSS version 27) the results of this study indicate that information technology has a positive and significant effect on MSME performance, information systems have a positive and significant effect on MSME performance, and simultaneously information technology and accounting Information Systems have a positive and significant effect on MSME Performance in Medan Johor District.